GROOMING KUCING DI LABORATORIUM KLINIK HEWAN JOGJA BULAN JULI â DESEMBER 2013 - , MARHAENDRA S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of catâs treatment is grooming. Grooming for cat in order to eliminate damage hair so that cat does not need to do by licking the hair as the habit of cats and in decreases the negative effects for cat. The final paper aim tho know how grooming in Laboratorium Klinik Hewan Jogja run. The material that used to arrange this paper is the implementation of catâs grooming in Laboratorium Klinik Hewan Jogja during Petâs Job Training dated march 31 to April 5. The methods that used to collect the data are observation, documentation, interview and practice. Procedures of catâs grooming in Laboratorium Klinik Hewan Jogja starting froom registration. First patient must be registered in front office by administration staff. The second step is scaling patient scaled by paramedic then will be bring to cehck up. Doctor (veterinarian) will check the conditions of patient, it includes the temperature, general condition, CRT, membran mucosa, integument, limph nodes, cardiovascular, respiratory and others. Integument will be a main focus in grooming. If veterinarian find a serious ill in patient, grooming will be rescheduled (pending/cancel). The data record for 6 monts shows that July 2013 there were 29 patients, August 2013 : 28 patients, September 2013 : 48 patients, October 2013 : 64 patients, November 2013 : 98 patients and December 2013 : 95 patients. The data shows the grooming service in Laboratorium Klinik Hewan Jogja is increased month by month. Laboratorium Klinik Hewan Jogja has operational proceduresâs steps of grooming. They are ears cleaning, eyes cleaning, nail cutting, combing the hair before bathing, bathing with warm water and use treatment shampoo according to patientâs needed, according to the existing theory, catâs grooming in Laboratorium Klinik Hewan Jogja has fulfill all the requirements.